Allergic airway inflammation delays glioblastoma progression and reinvigorates systemic and local immunity in mice. Issue 3 (18th October 2022) - Poli, Aurélie; Oudin, Anaïs; Muller, Arnaud; Salvato, Ilaria; Scafidi, Andrea; Hunewald, Oliver; Domingues, Olivia; Nazarov, Petr V.; Puard, Vincent; Baus, Virginie; Azuaje, Francisco; Dittmar, Gunnar; et al.
Abstract: Background: Numerous patient‐based studies have highlighted the protective role of immunoglobulin E‐mediated allergic diseases on glioblastoma (GBM) susceptibility and prognosis. However, the mechanisms behind this observation remain elusive. Our objective was to establish a preclinical model able to recapitulate this phenomenon and investigate the role of immunity underlying such protection. Methods: An immunocompetent mouse model of allergic airway inflammation (AAI) was initiated before intracranial implantation of mouse GBM cells (GL261). RAG1‐KO mice served to assess tumor growth in a model deficient for adaptive immunity. Tumor development was monitored by MRI. Microglia were isolated for functional analyses and RNA‐sequencing. Peripheral as well as tumor‐associated immune cells were characterized by flow cytometry. The impact of allergy‐related microglial genes on patient survival was analyzed by Cox regression using publicly available datasets. Results: We found that allergy establishment in mice delayed tumor engraftment in the brain and reduced tumor growth resulting in increased mouse survival. AAI induced a transcriptional reprogramming of microglia towards a pro‐inflammatory‐like state, uncovering a microglia gene signature, which correlated with limited local immunosuppression in glioma patients. AAI increased effector memory T‐cells in the circulation as well as tumor‐infiltrating CD4 + T‐cells. The survival benefit conferred by AAI was lost in mice devoid of adaptive immunity. Conclusion: Our results demonstrate that AAI limits both tumor take and progression in mice, providing a preclinical model to study the impact of allergy on GBM susceptibility and prognosis, respectively. We identify a potentiation of local and adaptive systemic immunity, suggesting a reciprocal crosstalk that orchestrates allergy‐induced immune protection against GBM. Abstract : Allergy‐induced protection against GBM is recapitulated in a preclinical syngeneic mouse model. Allergic airway inflammation skews microglia toward pro‐inflammatory and antigen‐presenting like‐states, uncovering a gene‐signature in mice associated with improved patient survival and reduced local immunosuppression in glioma patients. Allergic airway inflammation promotes the recruitment of CD4 + T‐cells within the tumor microenvironment and mitigates glioma‐induced systemic immunosuppression.Abbreviations: AAI, allergic airway inflammation; GBM, glioblastoma; Neu, neutrophil; TME, tumor‐microenvironment.